Analysis Of The Influence Of United States Political Interest On The Murder Of General Qasem Soleimani - Siti Fadhilah (Mediasi: Journal of International Relations, 2021)
This research discusses the analysis of the political interests of the United States towardsIran with a case study of the assassination of General Qasem Soleimani. The dispute between thetwo countries began many years ago where the Iranian government wanted to break away fromthe exploitation of Iran led by Muhammad Musaddeq, until the Iranian revolution in 1979 led byAyatullah Khomaeni to make Iran a state of the Islamic Republic of Iran and an anti-UnitedStates state until it culminated in the assassination of General Qasem Soleimani in 2020,General Qasem Soleimani is the most respected general in Iran and the leader of the Al-Qudsforce which is also the most respected force in Iran, The assassination committed by the UnitedStates against General Qasem Soleimani is related to the interests of the United States, toproduce appropriate answers this research uses two concepts namely foreign policy andoffensive realism, The method used is qualitative explanative by taking data from books,scientific journals, and websites. Foreign policy is an attempt by a country to achieve itsnational interests and how a country's national goals are obtained. Meanwhile, offensiveRealism is how a country with great power can maintain its power. The results of this studyexplain that the United States' political interest in Iran is an increase in United States politics inthe Middle East and Minimizes Terrorism Attacks against the United States. According to theUnited States General Qasem Soleimani and the Al-Quds Force are as dangerous in the politicaldevelopments of the United States as have been the case in Syria and Yemen, and the attacks aresuch dangerous for United States citizens that the United States has included the IRGC, theIranian Revolution Guard Corps) on its international terrorist list in 2019.